2020
DOI: 10.1101/2020.09.09.289132
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geospatial HIV-1 subtype C gp120 sequence diversity and its predicted impact on broadly neutralizing antibody sensitivity

Abstract: Evolving diversity in globally circulating HIV-1 subtypes presents formidable challenge in defining and developing neutralizing antibodies for prevention and treatment. HIV-1 subtype C is responsible for majority of global HIV-1 infections. Broadly neutralizing antibodies (bnAbs) capable of neutralizing distinct HIV-1 subtypes by targeting conserved vulnerable epitopes on viral envelope protein (Env) are being considered as promising antiviral agents for prevention and treatment. In the present study, we exami… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…1 a; top left). This observation also corroborates with our earlier finding [ 39 ]. The neutralization scores (IC 50 values) against VRC01, CAP256-VRC26.25, PGDM1400 and PGT121 of most of the same retrieved gp160 sequences of all subtypes were next obtained from the CATNAP database for the purpose of comparing with that obtained in the current study.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…1 a; top left). This observation also corroborates with our earlier finding [ 39 ]. The neutralization scores (IC 50 values) against VRC01, CAP256-VRC26.25, PGDM1400 and PGT121 of most of the same retrieved gp160 sequences of all subtypes were next obtained from the CATNAP database for the purpose of comparing with that obtained in the current study.…”
Section: Resultssupporting
confidence: 94%
“…Subtype C being the most predominant subtype circulating majorly in Africa and India, a greater understanding of the antigenic and neutralization diversity of HIV-1 subtype C env would facilitate understanding of optimal bnAb combination that could potentially overcome region-specific the intra-clade C diversity. Our recent work has demonstrated genotypic distinctness of HIV-1 subtype C envelope (gp120) sequences reported from Indian and African epidemics [ 39 ]. In that study, we observed these sequences to be distinct in terms of variable loop lengths (V1, V2 and V4), an abundance of potential N-linked glycosylation sites and entropy at bnAb contact sites (including PGDM1400 and CAP256-VRC26.25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A; top left). This observation also corroborates with our earlier nding [39]. The neutralization scores (IC 50 values) against VRC01, CAP256-VRC26.25, PGDM1400 and PGT121 of most of the same retrieved gp160 sequences of all subtypes were next obtained from the CATNAP database for the purpose of comparing with that obtained in the current study.…”
Section: Resultssupporting
confidence: 89%
“…Potential N linked glycosylation sites were predicted using N-Glycosite tool available at the LANL HIV database [45]. Statistics regarding the antibody resistance associated signature residues were generated as described recently [39]. A phylogenetic tree was generated for all the HIV-1 viral clone sequences available in the CATNAP database along with those generated in the present study (Total N= 1020) with iqtree under 'HIVb' model with estimated parameters and number of invariable sites [46].…”
Section: Sequence Analysismentioning
confidence: 99%